Empowering EFL Learners in Translation through Peer Review-based Instruction: A Case Study in Higher Education - Permana, Sudarya (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Although peer review can never substitute teacher feedback, it can become an alternative way for assessing EFL students’ completed tasks in view of that teachers often do not have enough time to give immediate feedback to the tasks. The present study aimed at finding out to what extent peer review was able to empower EFL learners, especially in translation classes. The research design was a case study which involved students’ translation analysis and questionnaire completion in data collection. Students’ translations were analyzed by using a content analysis technique which referred to the acceptability of translation, whereas student questionnaire with the technique of frequency count. The result showed that involving peer review in translation was able to empower EFL learners in two dimensions, i.e., lingual empowerment and personal empowerment. Lingual empowerment concerned students’ translation improvement in which it was regarded as an acceptable translation. Personal empowerment dealt with students’ psychological conditions in which they felt capable (empowered) of doing translation acknowledged from their positive responses to the involvement of peer review in translation. Considering the practical implications, teachers are suggested to employ a peer review in their translation classes. Peer review-based activities create translating opportunities where students can empower themselves, either lingually or personally.